Prediction Models for the Elastic Modulus of Fiber-reinforced Polymer Composites: An Analysis (Journal of Scientific Research, 2011)
An analysis has been done on the existing models for the prediction of the elastic modulus of fiber-reinforced polymer composites (FRPC). The experimental data reported in different specialized research journals have been fitted to the models. It is found the theoretical models such as the Parallel, Series and Halpin-Tsai model, by no means, predict the modulus within an acceptable deviation factor of 0.1. The semi-empirical models such as modified Halpin-Tsai and Bowyer-Bader model, which have one adjustable parameter, and are expressed in terms of volume fraction describe the modulus satisfactorily. In this paper, a mass fraction based model with one adjustable parameter is proposed, which also describe the modulus successfully. The proposed model, being mass fraction-based, is more convenient to work with than any volume-fraction based model, and unlike all other models (theoretical and semi-empirical), it has the potentials to have practical applications in structural material design.Keywords: Fibers; Polymer-matrix composites (PMCs); Short-fiber composites; Mechanical properties;   Prediction model.© 2011 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved.doi:10.3329/jsr.v3i2.6881                J. Sci. Res. 3 (2), 225-238 (2011)